Risk of Dementia in Patients with Depression or Parkinson’s Disease: A Retrospective Cohort Study - Ting-Chun Fang; Yu-Hsuan Wu; Yi-Huei Chen; Ching-Heng Lin; Ming-Hong Chang (Parkinson's Disease)
Background. This study aimed to clarify whether Parkinson’s disease (PD) and depression were independent risk factors or with synergic effects in dementia. Methods. Newly diagnosed PD (n = 1213) patients and control subjects (n = 4852) were selected from the Taiwan National Health Insurance Research Database from January 2001 through December 2008. Follow-up ended in 2011 with an outcome of dementia occurring or not. This cohort was divided into controls with or without depression, PD only, and PD with depression. The incident rate of dementia and hazard ratio (HR) using Cox’s regression analysis were calculated for each group. Results. When compared with controls without depression as HR 1.00, the adjusted HR for dementia was 3.29 (p<0.001) in the PD only group, 2.77 (p<0.001) in the PD with depression group, and 1.55 (p=0.024) in the depression only group. The incident rate of dementia was 29.2 (per 1000 person-years) in the PD only group and 13.2 in the PD with depression group. The effect of PD on dementia in the depression group produced a HR of 0.97 (p=0.905). Conclusions. Parkinson’s disease served as a risk factor for dementia. By comparison, depression was not a risk factor for dementia in PD patients, although it did act as a risk factor for dementia.